Emotional experience in uncomfortable indoor environments: A combined examination of personal factors - Kim, Hakpyeong; Hong, Taehoon (Building and environment, 2023)
Emotional experience is a critical element in human perception and interaction with the social environment. These experiences, while partially determined by internal human processes, are also influenced by physical environmental factors. This study aimed to investigate the impact of unfavorable environmental conditions on emotional experiences, considering personal factors. To achieve this, we recruited 52 subjects and conducted experiments using a climate chamber capable of simulating various environmental exposure scenarios. The subjects assessed their emotional experiences in real-time using a joystick annotator while viewing 30 emotion-evoking video stimuli, each clip lasting 10 s. This process was conducted under seven different environmental conditions within the chamber, including varying temperature and lighting conditions. The study aimed to answer two key research questions: (i) does the indoor environment significantly interfere with the self-perceived emotional experience of individuals exposed to it? and (ii) can personal factors modulate the emotional experience of individuals exposed to an indoor environment? This study found that an uncomfortable thermal environment tends to increase the intensity of human emotional experience, and individuals who are low in neuroticism and extraversion but high in satisfaction with the environment are more likely to have a misperception of emotional experience. Also, an uncomfortable lighting environment not only increased the intensity of human emotional experience but also changed the emotional aspects, and those with low agreeableness and conscientiousness tended to misunderstand emotional experiences. •Environmental and personal factors significantly influence emotional experiences.•Emotional experience to stimuli were recorded via a joystick annotator.•Unpleasant thermal and lighting environments amplify emotional intensity.•Low neuroticism and extraversion have emotional misperception in uncomfortable temperature.•Low agreeable and conscientious have emotional misperception in uncomfortable lighting.